Catalytic evaluation of citrate-stabilized palladium nanoparticles in the Sonogashira reaction for the synthesis of 1,4-Bis[(trimethylsilyl)ethynyl]benzene - Erick Gálvez-Martínez (Catalysis Communications, 2021)
Citrate-stabilized palladium nanoparticles were synthesized and supported on silica spheres. Conditions affecting particle size, stability and adsorption on silica particles are explored. The catalytic activity of nanoparticles in suspension as well as on silica support was evaluated in the Sonogashira reaction for the synthesis of 1,4-bis[(trimethylsilyl)ethynyl]benzene as a model and compared with conventional homogeneous catalysts. Unsupported particles presented very high catalytic activity and conversion with lower catalyst load despite their poor colloidal aggregation stability. Immobilized particles presented very good and, in some cases, superior catalytic performance than the most widely-used homogeneous catalysts, but using one order of magnitude less load. Successful catalyst recovery allowed its reuse in at least five consecutive reaction cycles with only 5–10% of activity loss. Fabrication nuances are considered for feasible catalyst preparation on a laboratory scale.